Answer:
8 = x
y = 29
Step-by-step explanation:
4x + 17 = y + 20 because vertical angles theorem.
y + 20 = 5x + 9 because interior angles theorem.
4x + 17 = 5x + 9 because same side interior angles theorem.
Subtract 9 from both sides and subtract 4x from both sides.
8 = x
Plug 8 in for x and solve.
5 times 8 is 40, plus 9 equals 49. Subtract 20 from both sides and you get 29.
5(8) + 9 = y + 20
49 = y + 20
29 = y
I hope this helps!
#teamtrees #WAP (Water And Plant)
Answer:
Step-by-step explanation:
a/b=4/5 b/c=2/9
Ration of a to c is
a/c=4/9
Answer:
<h2>12</h2>
Step-by-step explanation:
![nxy\div m\\\\n =3/4\\x =8\\y =6\\m=3\\\\\frac{3}{4} \times 8 \times 6 \div 3\\\\\mathrm{Divide\:the\:numbers:}\:6\div \:3=2\\=\frac{3}{4}\times \:8\times \:2\\\\\mathrm{Convert\:element\:to\:fraction}:\quad \:8=\frac{8}{1}\\=2\times \frac{3}{4}\times \frac{8}{1}\\\\\mathrm{Convert\:element\:to\:fraction}:\quad \:2=\frac{2}{1}\\=\frac{3}{4}\times \frac{8}{1}\times \frac{2}{1}\\\\Multiply\:fractions\\=\frac{3\times \:8\times \:2}{4\times \:1\times \:1}\\\\=\frac{48}{4}\\\\Simplify\\=12](https://tex.z-dn.net/?f=nxy%5Cdiv%20m%5C%5C%5C%5Cn%20%3D3%2F4%5C%5Cx%20%3D8%5C%5Cy%20%3D6%5C%5Cm%3D3%5C%5C%5C%5C%5Cfrac%7B3%7D%7B4%7D%20%5Ctimes%208%20%5Ctimes%206%20%5Cdiv%203%5C%5C%5C%5C%5Cmathrm%7BDivide%5C%3Athe%5C%3Anumbers%3A%7D%5C%3A6%5Cdiv%20%5C%3A3%3D2%5C%5C%3D%5Cfrac%7B3%7D%7B4%7D%5Ctimes%20%5C%3A8%5Ctimes%20%5C%3A2%5C%5C%5C%5C%5Cmathrm%7BConvert%5C%3Aelement%5C%3Ato%5C%3Afraction%7D%3A%5Cquad%20%5C%3A8%3D%5Cfrac%7B8%7D%7B1%7D%5C%5C%3D2%5Ctimes%20%5Cfrac%7B3%7D%7B4%7D%5Ctimes%20%5Cfrac%7B8%7D%7B1%7D%5C%5C%5C%5C%5Cmathrm%7BConvert%5C%3Aelement%5C%3Ato%5C%3Afraction%7D%3A%5Cquad%20%5C%3A2%3D%5Cfrac%7B2%7D%7B1%7D%5C%5C%3D%5Cfrac%7B3%7D%7B4%7D%5Ctimes%20%5Cfrac%7B8%7D%7B1%7D%5Ctimes%20%5Cfrac%7B2%7D%7B1%7D%5C%5C%5C%5CMultiply%5C%3Afractions%5C%5C%3D%5Cfrac%7B3%5Ctimes%20%5C%3A8%5Ctimes%20%5C%3A2%7D%7B4%5Ctimes%20%5C%3A1%5Ctimes%20%5C%3A1%7D%5C%5C%5C%5C%3D%5Cfrac%7B48%7D%7B4%7D%5C%5C%5C%5CSimplify%5C%5C%3D12)
Answer:
u=0.375
Step-by-step explanation:
First we can write the equation down, -6(-4u+4)-6u=2(u-5)-8. First what you want to do is distribute -6 to (4u+4) and 2 to (u-5). This would result in 24u-24-6u=2u-10-8. Next add up all like terms and you will get 18u-24=2u-18. Next you would want to add 24 on both sides so that you get 18u=2u+6 then subtract 2u from both sides to get 16u=6. You the divide 16 on both sides to get u=0.375.
14 because u are adding both factor and u are adding